2013
DOI: 10.1371/journal.pone.0075083
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-Wide Association Analysis with Gray Matter Volume as a Quantitative Phenotype in First-Episode Treatment-Naïve Patients with Schizophrenia

Abstract: Reduced Gray matter (GM) volume is a core feature of schizophrenia. Mapping genes that is associated with the heritable disease-related phenotypes may be conducive to elucidate the pathogenesis of schizophrenia. This study aims to identify the common genetic variants that underlie the deficits of GM volume in schizophrenia. High-resolution T1 images and whole genome genotyping data were obtained from 74 first-episode treatment-naïve patients with schizophrenia and 51 healthy controls in the Mental Health Centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Other than these regions, the cerebellum was traditionally supposed to be involved only in motor functions, but some studies have suggested its role in cognition and emotion [38] as well as in schizophrenia [39] . For example, abnormalities in the cerebellum and the occipital visual cortex have been detected in first-episode and/or drug-naïve patients [37,[40][41][42][43] using either the ROI approach or the voxel-based morphometry (VBM) method. In this study, the main effect of diagnosis on GMV suggested that the GM defi cits in schizophrenia might involve widespread regions and circuits in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Other than these regions, the cerebellum was traditionally supposed to be involved only in motor functions, but some studies have suggested its role in cognition and emotion [38] as well as in schizophrenia [39] . For example, abnormalities in the cerebellum and the occipital visual cortex have been detected in first-episode and/or drug-naïve patients [37,[40][41][42][43] using either the ROI approach or the voxel-based morphometry (VBM) method. In this study, the main effect of diagnosis on GMV suggested that the GM defi cits in schizophrenia might involve widespread regions and circuits in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…26 Evidence suggests that the risk for schizophrenia involves many genetic variants, each with small effects, 27 and the size of cohorts required to identify individual SNPs with such small effects is prohibitive. 28 Recent evidence, however, suggests that better homogeneity among cohorts could be more important than increasing sample sizes.…”
Section: J Psychiatry Neurosci 2017;42(3)mentioning
confidence: 99%
“…1 Some measures of brain development, such as total brain volume, show strong heritability, while others, such as subcortical gray matter volume, show weaker heritability. [12][13][14] Recent large studies that have identified single nucleotide polymorphisms (SNPs) implicated in N-methyl-d-aspartate (NMDA) and dopamine signaling have shown robust associations with volumes of adult putamen and hippocampal brain regions, respectively. [12][13][14] Recent large studies that have identified single nucleotide polymorphisms (SNPs) implicated in N-methyl-d-aspartate (NMDA) and dopamine signaling have shown robust associations with volumes of adult putamen and hippocampal brain regions, respectively.…”
Section: Introductionmentioning
confidence: 99%